UTILIZING MYSTERY BOX MEDIA TO IMPROVE ENGLISH SPEAKING PROFICIENCY AT MAYJEND SUTOYO SCHOOL - Henokh Febio Hutagalung; Azizah Husda; Rony Arahta Sembiring (English Language Teaching Prima Journal (ELT), 2024)
This research aims to assess the effectiveness of using mystery box media to improve English speaking skills among eighth-grade students at Mayjend Sutoyo Middle School in Medan. The study employs a Classroom Action Research (CAR) approach, encompassing three phases: Pre-cycle, Cycle 1, and Cycle 2. This methodology allows for a comprehensive evaluation of the strategy's impact on student engagement and performance. Data collection methods include observations, speaking rubric evaluations, and documentation analysis. The results indicate a marked enhancement in students' speaking abilities following the implementation of the Mystery Box strategy. These outcomes highlight the value of interactive, game-based learning techniques in fostering English speaking proficiency. Future studies might investigate the prolonged effects of this method on students' overall language development.